Visual Inquiry of Symbolic Universes : Thirty Years of Visual Anthropology in Sardinia in the Images of Dario Coletti - Bobò, Gaia (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2023)
The article aims to retrace possible intersections between visual cultures and anthropology in the Mediterranean through empirical and critical research on the photographic practice of the Italian photographer Dario Coletti (Rome, 1959). In his massive body of work, Coletti established an archive of visual narrations of the living culture of the island’s inhabitants, from the working conditions of the miners and of the communities of fishermen to the traditional local celebrations, such as the Carnivals and the Holy Weeks. In particular, the photographic series Mana. Cronache dal carnevale barbaricino 1995-2015, focusing on the depiction of the Carnival of Barbagia, is here analyzed for its outstanding role within the author’s production. The appendix of the article includes the contributions of Antonio Cecere, Giulio Latini, and Paolo Quintili contextualizing Coletti’s practice within the field of Mediterranean studies, as well as providing its possible intersection with anthropology, philosophy, and media studies.